Status Epilepticus Enhances Depotentiation after Fully Established LTP in an NMDAR-Dependent but GluN2B-Independent Manner. (3rd January 2016) - Guli, Xiati; Tokay, Tursonjan; Kirschstein, Timo; Köhling, Rüdiger
Abstract : N-Methyl-D-aspartate (NMDA) receptor-dependent long-term potentiation (LTP) can be reversed by low-frequency stimulation (LFS) referred to as depotentiation (DP). We previously found GluN2B upregulated in CA1 neurons from post-status epilepticus (post-SE) tissue associated with an enhanced LTP. Here, we tested whether LFS-induced DP is also altered in pathological GluN2B upregulation. Although LTP was enhanced in post-SE tissue, LTP was significantly reversed in this tissue, but not in controls. We next tested the effect of the GluN2B subunit-specific blocker Ro 25-6981 (1 μ M) on LFS-DP. As expected, LFS had no effect on synaptic strength in the presence of the GluN2B blocker in control tissue. In marked contrast, LFS-DP was also attained in post-SE tissue indicating that GluN2B was obviously not involved in depotentiation. To test for NMDA receptor-dependence, we applied the NMDA receptor antagonist D-AP5 (50 μ M) prior to LFS and observed that DP was abolished in both control and post-SE tissue confirming NMDA receptor involvement. These results indicate that control Schaffer collateral-CA1 synapses cannot be depotentiated after fully established LTP, but LFS was able to reverse LTP significantly in post-SE tissue. However, while LFS-DP clearly required NMDA receptor activation, GluN2B-containing NMDA receptors were not involved in this form of depotentiation.